Amikacin: a Rapid and Sensitive Radioimmunoassay - Lewis, John E. (1975)
A rapid, sensitive, and specific radioimmunoassay has been developed for the measurement of amikacin, a new semisynthetic aminoglycoside antibiotic. Antisera were produced by immunizing rabbits with amikacin conjugated to porcine thyroglobulin. Sera were screened for amikacin antibodies with (3)H-labeled amikacin. Free and bound radioactivity were separated by the second antibody method. As little as 5 ng of the antibiotic can be measured in serum, cerebrospinal fluid, and urine. The standard curve is unaffected by pH (5–11), ionic strength (0.01 M to 0.3 M), MgCl(2) or CaCl(2) (1 to 8 mM/liter), or urea (10–300 mg/100 ml). The antibodies raised to amikacin are not able to distinguish between kanamycin and amikacin. The cross reactivity of all other antibiotics tested was <0.1%. Co-incubation of first and second antibody allows for a 30-min incubation period, making the assay useful for stat determinations. The standard curve is linear on a logit-log plot, allowing for rapid computer analysis of the standard curve, interpolation of sample values, and quality-control monitoring.